Marginal bone loss one year after implantation: a systematic review of different loading protocols. Issue 1 (January 2020) - Sommer, M.; Zimmermann, J.; Grize, L.; Stübinger, S.
Abstract: The aim of this study was to analyse the influence of different loading protocols on marginal bone loss (MBL). The outcomes of different implant loading protocols were assessed at 1 year after implantation, with focus on MBL; protocols included immediate, immediate non-occlusal, early, and conventional loading. The search strategy resulted in 889 studies. Twenty-two of these studies fulfilled the inclusion criteria. Among the included studies, the lowest MBL was for immediately loaded implants (0.05 ± 0.67 mm) and the highest for immediate non-occlusally loaded implants (1.37 ± 0.5 mm). The results of the meta-analysis showed an estimated mean MBL of 0.457 mm (95% confidence interval (CI) 0.133–0.781) for immediate loading, 0.390 mm (95% CI 0.240–0.540) for immediate non-occlusal loading, 0.488 mm (95% CI 0.289–0.687) for early loading (>2 days to <3 months), and 0.852 mm (95% CI 0.429–1.275) for conventional loading (>3 months) implant protocols. The lowest decrease in 1-year implant survival per millimetre increase in MBL was observed for immediate loading and the highest for conventional loading. Conventional loading showed a significantly higher MBL than the other three loading protocols. This systematic review and meta-analysis indicates that the immediate loading protocol is a reasonable alternative to the conventional loading protocol.